Europejski Fundusz Rozwoju Regionalnego jako źródło finansowania inwestycji oświatowych samorządu gminnego (na przykładzie gmin województwa wielkopolskiego) - Gońda, Ewa (The European Regional Development Fund as a Source of Financing Educational Investment Projects Pursued by Commune Self-Government (Based on the Examples of Communes in the Wielkopolska Voivodship), 2006)
Since Poland joined the European Union, the Polish communes have been offered an opportunity to use an additional source of financing their educational investment projects, namely the EU structural funds. This study has been aimed at demonstrating the possibilities of financing such investment from the resources provided by the largest structural fund, i.e. the European Regional Development Fund. The author has attempted to find out about the range these opportunities were used by communes in the Wielkopolska voivodship in the process of the first selection of applications submitted after Poland's to the accession EU. Considerations presented in this study demonstrate that commune authorities in the Wielkopolska voivodship, and in particular organs of rural communes, showed active involvement in the process of applying for ERDF subsidies for their educational investment projects and produced well prepared applications.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 551-559